2010
DOI: 10.1111/j.1476-5381.2010.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐administration of ibuprofen and nitric oxide is an effective experimental therapy for muscular dystrophy, with immediate applicability to humans

Abstract: Background and purpose: Current therapies for muscular dystrophy are based on corticosteroids. Significant side effects associated with these therapies have prompted several studies aimed at identifying possible alternative strategies. As inflammation and defects of nitric oxide (NO) generation are key pathogenic events in muscular dystrophies, we have studied the effects of combining the NO donor isosorbide dinitrate (ISDN) and the non-steroidal anti-inflammatory drug ibuprofen. Experimental approach: a-Sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 63 publications
1
36
0
1
Order By: Relevance
“…The results of the ISOFEN1 study confirmed the optimal tolerability of the combined therapy with ibuprofen and ISO previously documented in a pilot study in dystrophic patients 23. In mouse models of DMD, the effect of ISO plus ibuprofen is endowed with a synergistic therapeutic effect 25,26. The similar pharmacokinetic profiles of ibuprofen and ISO, when given alone or combined, allow us to exclude that the synergism between these two drugs is eventually related to an unmasked pharmacokinetic drug-to-drug interaction.…”
Section: Discussionsupporting
confidence: 73%
“…The results of the ISOFEN1 study confirmed the optimal tolerability of the combined therapy with ibuprofen and ISO previously documented in a pilot study in dystrophic patients 23. In mouse models of DMD, the effect of ISO plus ibuprofen is endowed with a synergistic therapeutic effect 25,26. The similar pharmacokinetic profiles of ibuprofen and ISO, when given alone or combined, allow us to exclude that the synergism between these two drugs is eventually related to an unmasked pharmacokinetic drug-to-drug interaction.…”
Section: Discussionsupporting
confidence: 73%
“…The pharmacological properties of molsidomine may also contribute to explain the higher efficacy of this drug with respect to other NOdonating or NO-generating drugs investigated in the past as therapeutic approaches to muscular dystrophy, i.e. the NOS substrate L-arginine and the NO donor isosorbide dinitrate (Barton et al, 2005;Hnia et al, 2008;Marques et al, 2005;Sciorati et al, 2010;Voisin et al, 2005). The release of NO from molsidomine has a slower onset and is more prolonged than with isosorbide dinitrate (Agvald et al, 1999) and, at variance with isosorbide dinitrate, it occurs independently of interactions with thiolcontaining compounds (Noack and Feelisch, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…We found that for NO release to have significant and persistent therapeutic effects it has to be combined with non steroidal anti-inflammatory (NSAID) activity; the combination of these pharmacological activities resulted in an increased muscle progenitor differentiation, survival and selfrenewal and quenching of inflammation all contributing to effective muscle repair (Brunelli et al, 2007;Sciorati et al, 2010;Sciorati et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…up to the end of the observation period, which was set at 12 months to mimic a chronic treatment in a clinical setting with patients. Several mechanisms synergised to yield the therapeutic effect of the combined therapy: significant reduction in both fibre damage and inflammation and increases in the myogenic precursor cells number and differentiation capacity, which preserve the long-term regeneration capacity of muscle [119][120][121]. Other actions of NO on skeletal muscle such as vasodilation and thus reduction of the ischaemia induced by nNOS displacement, increase in glucose uptake and in energy generation [106] may also have contributed to muscle repair.…”
Section: Nitric Oxide and The Therapy Of Muscular Dystrophiesmentioning
confidence: 93%